Data-driven estimation of energy consumption for electric bus under real-world driving conditions. (September 2021) - Chen, Yuche; Zhang, Yunteng; Sun, Ruixiao
Highlights: Develop models to predict 1 Hz energy consumption of electric buses. Establish long short-term memory and artificial neural network models. Train and cross-validate models using a long-term electric bus monitoring dataset. Abstract: Reliable and accurate estimation of an electric bus's instantaneous energy consumption is critical in evaluating energy impacts of planning and control of electric bus operations. In this study, we developed machine learning-based long short-term memory (LSTM) and artificial neural network (ANN) models to estimate 1 Hz energy consumption of electric buses based on continuous monitoring data of electric buses in Chattanooga, Tennessee, in 2019 and 2020. We propose a data-partitioning algorithm to separate energy charging and discharging modes before applying data-driven estimation models. A K -fold cross-validation-based model selection process was conducted to identify the optimal model structure and input variables in terms of prediction accuracy. The estimation results show the predicted mean absolute percentage error rates of LSTM and ANN models were 3% and 5%, respectively. We compared the proposed models with existing models in the literature based on the same testing data to demonstrate the predictability of our models.